Pengaruh Kecakapan Manajerial, Good Corporate Governance Dan Book Tax Differences Terhadap Kualitas Laba Perbankan Di Indonesia - Ando Suryo Wicaksono; Isna Putri Rahmawati (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2019)
The purpose of this research was to find out relationship between managerial ability, good corporate governance and book tax differences with earnings quality on of conventional banking industry. Samples were selected by purposive sampling using criteria conventional banks which listing in Indonesia Stock Exchange during 2014-2017. This research showed that GCG had positive signifficant effect on earnings quality, while managerial ability and book tax differences had no signifficant effect on earnings quality. This research analyzed firm size as control variabel, which showed negative effect on earnings quality.